Penggunaan Perisian Atlas.ti 8 Dan Maktabah Syamilah Dalam Kajian Kualitatif Bahasa Arab - Khairul Asyraf Mohd Nathir; Mohd Sukki Othman; Nik Farhan Mustapha; Wan Muhammad Wan Sulong (PIMM Experts Sdn Bhd, 2024)
Volume : 5 No: 2